Thermal and high-pressure stability of purified pectin methylesterase from plums (Prunus domestica) - Nunes, Claudia S.
Pectin methylesterase (PME) from greengage plums (Prunus domestica) has been extracted and purified using affinity chromatography. Only one band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis was obtained, with an estimated molecular weight of 31 kDa. On isoelectric focusing electrophoresis, two bands with neutral isoelectric points (6.8 and 7.0) were detected. The optimal pH and temperature for plum PME activity were 7.5 and 65C, respectively. A study of purified plum PME thermostability was performed at pH 7.5 and 4.0, indicating a higher thermostability at pH 7.5 than at pH 4.0. A biphasic inactivation behavior was observed for thermal treatments (54-70C), whereas its pressure inactivation could be described by a first-order kinetic model in a pressure range of 650-800 MPa at 25C. Purified plum PME was found to be relatively stable to thermal and pressure (</=600 MPa) treatments, compared to PME from other fruits.